Digital wavefront recording, reconstruction and 3D display - Qian, Kemao (2010)
In this report, we summarize the work we have done under the support of SUG 15/06: Digital wavefront recording, reconstruction, and 3D display. The importance of the project is from the fact that phase of optical wavefronts are more important in precision metrology, though we sense the amplitude of optical wavefronts every day. Thus the objective of the project is measure, analyze and display the phase. Throughout the investigation, we have the following achievements: